Predicting the Flood Hydrographs of Ungauged Watersheds Using the - T S; R A; A SH; A T (مهندسی منابع آب, 2009)
Developing a rainfall-runoff model for an ungauged watershed provides the opportunity to estimate the peak flow, flood volume and flood hydrograph for that watershed. In this study, a rainfall-runoff model was developed for the Kasilian Watershed in the province of Mazandaran northern iran using the GIS system, the SCS method and the HEC-HMS hydrologic model. By using the HEC-GeoHMS extension and the digital elevation model (DEM) in the geographic information system domain (ARCVIEW software), the physiographic model, the sub-basin boundaries and stream networks for the Kasilian Watershed were defined. By incorporating the soil hydrologic group and land use maps, and the initial moisture content information in the GIS system, the curve number (CN) diagram of the Kasilian Watershed sub-basins was prepared. The SCS method was selected for simulating the flood hydrograph, and the Lag method was used for river routing. The watershed physiographic model was transferred from the GIS system to the HEC-HMS program, and the hydrologic model for the watershed was determined. By using several rainfall events and the observed flood hydrographs, the parameters of the watershed hydrological model, including initial loss and lag time of the sub-basins, were optimized. using to the mean optimized parameters, the model was evaluated for three different rainfall events. The developed model accurately predicted the values used in constracting the flood hydrographs for 2 events. However, that for the 3nd event had an error range of 10-15%, which were within the acceptable range.